Biogenic nanosilver inhibits Mycobacteria using nitrate reductase assay. (23rd August 2019) - Bello, Adebayo J.; Adams, Luqman A.; Onyejepu, Nneka N.; Igbinehi, Justice I.; Igbari, Omoboyede F.; Okpuzor, Joy
Nanosilver was synthesised by bioreduction using aqueous extracts of Moringa oleifera (MO-AgNPs) leaf and Allium cepa bulb (AC-AgNPs) as reducing and capping agents. The nanosilver was characterised with UV/vis, FT-IR, and SEM-EDX. Microbiological activity on five Mycobacteria strains: ATCC 35882, ATCC 25177, Mycobacterium other than tuberculosis (MOTT), Mycobacterium fortuitum and multi drug resistance M. tuberculosis (MDR-MTB) was investigated using nitrate reductase assay (NRA). Results obtained for UV/vis gave absorption maxima at 430 nm for MO-AgNPs and 440 nm for AC-AgNPs. FT-IR showed functional groups associated with the biomolecular capping agents. SEM showed the nanosilver formed aggregates spherical and/or in oval shape with smooth surface. EDX spectra exhibited the presence of elemental silver. Minimum inhibitory concentration (MIC) study for both nanosilver against Mycobacteria indicated a higher inhibitory activity for MO-AgNPs over the AC-AgNPs. Herein, we have reported the first biosynthesised nanosilver activity against Mycobacteria using NRA. Nanosilver may therefore be developed as nanoaerosol for targeted and effective treatment of Mycobacteria infections.